Test case prioritization based on data reuse for Black-box environments - Lima, Lucas Albertins de (2009)
Albertins de Lima, Lucas; Cezar Alves Sampaio, Augusto. Test case prioritization based on data reuse for Black-box environments. 2009. Dissertação (Mestrado). Programa de Pós-Graduação em Ciência da Computação, Universidade Federal de Pernambuco, Recife, 2009.